1990
DOI: 10.1177/0013164490504001
|View full text |Cite
|
Sign up to set email alerts
|

Tests for Normality and Measures of Skewness and Kurtosis: Their Place in Research Reporting

Abstract: Even though research interest is typically greatest for questions pertaining to central tendency and, to a lesser degree, variability, knowledge about the nature of a measure or variable is impoverished when information about the shape of the frequency distribution is ignored. This paper makes the point that descriptive and inferential measures of non-normality should be a routine part of research reporting, along with graphic displays of the frequency distribution of important variables. This point is especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(117 citation statements)
references
References 11 publications
1
103
0
13
Order By: Relevance
“…KR was also robust for the interaction effect, although with a total sample size of 30, it was mainly liberal, but again independently of the degree of kurtosis or violation of the sphericity assumption. These findings are partially consistent with research that has reported the effect of kurtosis on the robustness of other statistical tests (Harwell et al, 1992;Hopkins & Weeks, 1990). Although the present results show an effect of kurtosis on empirical type I error rates with small samples and in relation to the interaction effect, taken together they support previous studies Chafin & Rhiel, 1993;Scheffé, 1959) that have suggested that skewness effects are greater than those of kurtosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…KR was also robust for the interaction effect, although with a total sample size of 30, it was mainly liberal, but again independently of the degree of kurtosis or violation of the sphericity assumption. These findings are partially consistent with research that has reported the effect of kurtosis on the robustness of other statistical tests (Harwell et al, 1992;Hopkins & Weeks, 1990). Although the present results show an effect of kurtosis on empirical type I error rates with small samples and in relation to the interaction effect, taken together they support previous studies Chafin & Rhiel, 1993;Scheffé, 1959) that have suggested that skewness effects are greater than those of kurtosis.…”
Section: Discussionsupporting
confidence: 93%
“…However, the effect of kurtosis and skewness on the KR procedure has yet to be specifically explored. Some studies focusing on other statistical procedures have found that the effects of kurtosis are greater than those of skewness (Harwell, Rubinstein, Hayes & Olds, 1992;Hopkins & Weeks, 1990), whereas others have reported that the effects of skewness are greater than those of kurtosis Chafin & Rhiel, 1993;Scheffé, 1959).…”
mentioning
confidence: 99%
“…We identified deviations from normality for all four regressions and examined the mental health measures to evaluate whether problems with skewness might be accounting for the lack of normality. Variables were considered skewed if the variable's skewness statistic exceeded twice its standard error (Hopkins & Weeks, 1990). This was the case for all four measures.…”
Section: Weighting and Analysesmentioning
confidence: 99%
“…Platykurtic (flat) distributions have a flatter top and shorter and thinner tails while leptokurtic (sharp) distributions have a sharp top but longer and wider tails. Skewed distributions are always sleptokurtic (Hopkins and Weeks, 1990). An unbiased estimator of underlying kurtosis that works well for any n can be calculated as (Joanne and Gill, 1998) (…”
Section: Skew and Kurtosismentioning
confidence: 99%